Tsimtsum and modernity : lurianic heritage in modern philosophy and theology - Bielik-Robson, Agata; Weiss, Daniel (Berlin : De Gruyter, 2021)
This volume is the first-ever collection of essays dedicated to the Lurianic concept of tsimtsum. It includes eighteen studies in philosophy, theology, and intellectual history, showcasing the historical development and evolving meaning of this idea. The essays trace its journey from the Hebrew Bible and classical midrashic texts, through Kabbalah, Isaac Luria and his disciples, to its influence in modern thought. The contributors examine its impact on thinkers ranging from Spinoza, Böhme, Leibniz, Newton, Schelling, and Hegel, to Scholem, Rosenzweig, Heidegger, Benjamin, Adorno, Horkheimer, Levinas, Jonas, Moltmann, and Derrida.
Includes index.
Keywords: God (Judaism).; Jewish philosophy